PENGARUH PEMBERIAN TEH HITAM, TEH HIJAU (Camelia sinersis var. assamica),TEH DAUN MURBEI (Morus kanva) DAN CAMPURANNYA TERHADAP KADAR HEMOGLOBIN GLIKOSILAT DAN INSULIN PADA TIKUS DIABETES - Bait, Yoyanda (Jurnal Health and Sport, 2011)
Diabetes mellitus was a degenerative disease with a high prevalence that happened in many countries. Several studies had been done to control diabetes by using such as green tea, mulberry leaftea, and their mixtures. The aim of this study was investigated the effect of black tea green tea mulberry tea and their mixtures on glycosilated hemoglobin and insulin level. This experiment used fourty two rats, aged2.5-3.0 months, 150-200 g bw. The rats were divided into 7 groups, each group consisted of 3 rats, namely; normally control group, negative control group, black tea group, green tea group, mulberry leaf tea group, black tea+mulberry leaf tea group and green tea+mulberry leaf tea group. The study was carried out for 16 days intervention. The dose of alloxan 125 mg/kg bw were given by intraperitonial. After blood glucose level >200 mg/dl, rats were given tea with dose I ml/day/100 g bw. The results were showed that toa treatments were not significantly (p>0,05) affected to glycosilated hemoglobin level [HbAlc) and insulin level from rats blood.